The Family Mealtime Observation Study (FaMOS): Exploring the Role of Family Functioning in the Association between Mothers’ and Fathers’ Food Parenting Practices and Children’s Nutrition Risk - Walton, Kathryn (Nutrients, 2019)
This cross-sectional study explores associations between mothers’ and fathers’ food parenting practices and children’s nutrition risk, while examining whether family functioning modifies or confounds the association. Home observations assessed parents’ food parenting practices during dinnertime (n = 73 families with preschoolers). Children’s nutrition risk was calculated using NutriSTEP(®). Linear regression models examined associations between food parenting practices and NutriSTEP(®) scores. An interaction term (family functioning × food parenting practice) explored effect modification; models were adjusted for family functioning to explore confounding. Among mothers, more frequent physical food restriction was associated with higher nutrition risk in their children (β = 0.40 NutriSTEP(®) points, 95% Confidence Interval (CI) = 2.30, 7.58) and among both mothers and fathers, positive comments about the target child’s food were associated with lower nutrition risk (mothers: β = −0.31 NutriSTEP(®) points, 95% CI = −0.54, −0.08; fathers: β = −0.27 NutriSTEP(®) points, 95% CI = −0.75, −0.01) in models adjusted for parent education and child Body Mass Index (BMI) z-score. Family functioning did not modify these associations and they remained significant after adjustment for family functioning. Helping parents to use positive encouragement rather than restriction may help to reduce their children’s nutrition risk.